The Effect of Intellectual Capital on Firm Market Value (E-Jurnal Akuntansi, 2026)
This research investigates empirical effect of intellectual capital and market value of a company through the lens of resource-based theory. Intellectual capital is proxied by VAIC™, which encompasses human capital efficiency, structural capital efficiency, and capital employed efficiency. Technology sector companies on Indonesia Stock Exchange during 2022-2024 serve as the research object. Total of 69 observations were selected by purposive sampling. Multiple linear regression was used to analyze the data using SPSS. The findings discover that human capital efficiency and structural capital efficiency positively and significantly influence market value, whereas capital employed efficiency demonstrates significant negative association. These results imply that, within the technology industry, optimizing human resources and operational infrastructure exerts more influence on investor perceptions of firm value than efficient use of physical capital.
Keywords: Human Capital Efficiency; Structural Capital Efficiency; Capital Employed Efficiency; Nilai Pasar Perusahaan